2020
DOI: 10.3390/app10072515
|View full text |Cite
|
Sign up to set email alerts
|

Improved Active Disturbance Rejection-Based Decentralized Control for MIMO Nonlinear Systems: Comparison with The Decoupled Control Scheme

Abstract: A decentralized control scheme is developed in this paper based on an improved active disturbance rejection control (IADRC) for output tracking of square Multi-Input-Multi-Output (MIMO) nonlinear systems and compared with the decoupled control scheme. These nonlinear MIMO systems were subjected to exogenous disturbances and composed of high couplings between subsystems, input couplings, and uncertain elements. In the decentralized control scheme, it was assumed that the input couplings and subsystem couplings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This paper presented a novel approach to the design of a new class of LESO achieved by nesting an additional LESO in parallel with the original to obtain an N-ADRC. The proposed N-ADRC was successfully applied to the hypothetical SISO and a highly uncertain nonlinear SISO system with exogenous disturbance, as given in Equation (50). It can be concluded that the N-ADRC outperforms the C-ADRC in terms of control effort, output tracking, and disturbance rejection, as well as, more obviously, in the case of measurement error.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This paper presented a novel approach to the design of a new class of LESO achieved by nesting an additional LESO in parallel with the original to obtain an N-ADRC. The proposed N-ADRC was successfully applied to the hypothetical SISO and a highly uncertain nonlinear SISO system with exogenous disturbance, as given in Equation (50). It can be concluded that the N-ADRC outperforms the C-ADRC in terms of control effort, output tracking, and disturbance rejection, as well as, more obviously, in the case of measurement error.…”
Section: Discussionmentioning
confidence: 95%
“…In future work, this approach can be extended to nest more than two LESOs, and nonlinear ESOs could also be used and their performance investigated for multi-input-multi-output (MIMO) systems. Finally, several real-world nonlinear models can be used to show the performance of the N-ADRC as given in [45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The part of the system (12) that is different from the standard integral series is regarded as the total disturbance (including internal disturbance and external disturbance), thereby forming an integral series system with disturbance (13). ESO uses the system's input and output information to estimate the total disturbance and then compensates the total disturbance through the control law, thereby transforming the system (13) into a standard integral series system (18).…”
Section: ) Extended State Observer (Eso)mentioning
confidence: 99%
“…They selected the particle swarm technique (PSO) as an optimal tuner to improve the estimation process and, thereby, to enhance the system performance. Abdul-Adheem et al [18] designed an ADRC controller based on an improved extended state observer for MIMO systems and achieved good control results. In reference [19], Abdul-Adheem et al proposed a Novel Active Disturbance Rejection Control (N-ADRC) strategy that replaces the Linear Extended State Observer (LESO) used in Conventional ADRC (C-ADRC) with a nested LESO.…”
Section: Introductionmentioning
confidence: 99%
“…ADRC has small overshoot characteristics, fast response speed, high control precision, strong antidisturbance ability, and simple structure [15,16]. Reference [17] designed an ADRC based on an improved extended state observer for multiple-input multiple-output systems and achieved good control results. Reference [18] designed four improved ADRC for the nonlinear model of a 6-DOF quadrotor system for height and attitude stabilization and compared the PID controller's performance.…”
Section: Introductionmentioning
confidence: 99%